Developing Reading Skills Among Students with Learning Disabilities in English - Mohamad Ahmad Saleem Khasawneh (Journal La Edusci, 2021)
This research investigated developing the reading skills among students with learning disabilities in English language. The study sample included 20 male and female students from Irbid city, Jordan, who were chosen purposefully, and distributed randomly to two groups. The first group was the experimental group that was taught using the active learning method, and the other group was the control group that was taught according to the usual method. The study used a reading test, which was verified by presenting it to a group of judges. The reliability of the list was checked by using the test and re-test method and the Pearson's coefficient, which was (0.95). The findings revealed the presence of differences between the mean scores of the two study groups on the post-reading test, in favor of the experimental group. The results did not show any statistically significant differences between the mean scores of the two groups in the post-reading test due to the gender variable. In light of the findings of the study, the researcher recommends preparing training programs on active learning and preparing a guide for teachers, which can be used to teach and learn reading skills for students with learning disabilities.